Synthesis and Characterization of New Schiff Bases Ligands and Studies It’s Complexes with Some Elemintes - Mohmmed Hamid Said (Journal of Global Pharma Technology, 2019)
Preparation a new Schiff base ligand derived from reaction of terephthaldehyde with 2- aminobenzothiozol at (1:1) molar ratio and characterized by Uv-Vis, FT-IR, proton NMR and mass spectrometer and elemental analysis. The ligand mixed with Co (II), Ni (II), Cu (II), and Zn (II) chloride solutions at (2:1) molar ratio to form complexes. These complexes are characterized by elemental analysis, FT-IR, Uv-Vis, molar conductivity and magnetic sensitivity. This study concluded, the ligand acted as bidentate ligand, and all complexes have octahedral structuresKeywords: Terephthaldehyde, 2- aminobenzothiozol, Schiff base, Bidentate Ligand.